Nothing to Lose? An Examination of Prison Misconduct Among Life-Without-Parole Inmates - Sorensen, Jonathan R. (The prison journal, 2019)
Inmates serving life-without-parole (LWOP) have been described as having “nothing to lose” by virtue of their sentence, leading to an assumption that they are more prone to disciplinary violations. This study refutes such an argument and is consistent with research demonstrating that LWOP inmates do not pose a disproportional risk for disciplinary misconduct. Results from our study comparing LWOP with parole-eligible, life-sentenced (LWP) inmates revealed neither significant differences in the total violation count nor the time to commission of an act of disciplinary misconduct. Trajectories of misconduct showed slightly higher prevalence of misconduct among LWOP inmates, a pattern of declining prevalence during the first 18 months of confinement, and a convergence with LWP inmates thereafter. The failure of assumptions of high violence risk for LWOP inmates has important public policy and correctional implications.